Najkrótszy kurs tragikomedii PRL: Rejs Marka Piwowskiego - Obremski, Krzysztof (Przestrzenie Teorii, 2019)
The tragicomic finale to a costume ball on a ship sailing into night-time darkness was already ‚conceived’ when passengers first stepped onto the gangway. The Cruise is a mix of genres (as was known from the ancient geneological theory of genus mixtum), because situational comedy and sociodrama co-create a genre as broken as tragicomedy, hence „If Rejs is considered a comedy, do not forget that it is a mocking comedy, streaked with despair, as bitter as gall” (Marek Hendrykowski).